2023
DOI: 10.1002/ame2.12334
|View full text |Cite
|
Sign up to set email alerts
|

Biology and function of pericytes in the vascular microcirculation

Abstract: Pericytes are the main cellular components of tiny arteries and capillaries. Studies have found that pericytes can undergo morphological contraction or relaxation under stimulation by cytokines, thus affecting the contraction and relaxation of microvessels and playing an essential role in regulating vascular microcirculation. Moreover, due to the characteristics of stem cells, pericytes can differentiate into a variety of inflammatory cell phenotypes, which then affect the immune function. Additionally, pericy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Abnormal structure and function of miniscule arteries and capillaries results in hypoperfusion of blood flow (Mourad and Levy, 2011;Struijker-Boudier and Heijnen, 2011;Wu et al, 2023). Studies have shown that sparse microcirculation may be one of the main causes of hypertension (Ciuffetti et al, 2003).…”
Section: Relationship Between Microcirculation-induced Hypertension A...mentioning
confidence: 99%
“…Abnormal structure and function of miniscule arteries and capillaries results in hypoperfusion of blood flow (Mourad and Levy, 2011;Struijker-Boudier and Heijnen, 2011;Wu et al, 2023). Studies have shown that sparse microcirculation may be one of the main causes of hypertension (Ciuffetti et al, 2003).…”
Section: Relationship Between Microcirculation-induced Hypertension A...mentioning
confidence: 99%
“…Although ECs, which make up the innermost layer of blood vessels, can naturally form initial networks, the absence of pericyte recruitment causes these structures to rapidly deteriorate [ 33 , 123 ]. Pericytes have an important role to play in the regulation of vascular blood flow, regulation of the internal diameter of the vasculature, and vascular stabilization [ 124 , 125 ].…”
Section: Cell Source For Blood Capillary Formationmentioning
confidence: 99%
“…Pericytes are crucial for angiogenesis, influencing vessel stability by interacting with sprouting endothelial cells. They can also adjust capillary diameters, similar to smooth muscle cells, regulating microvessel blood flow [19].…”
Section: Angiogenesismentioning
confidence: 99%
“…They regulate the immune system in the central nervous system. Reduced CD4+ T-cells lead to decreased pericyte coverage, and retinal pericytes inhibit CD4+ T-cell activation [19].…”
Section: Impact On Immune Functionmentioning
confidence: 99%